Literatura para brincar: Ultimo round, de Julio Cortázar - Bianka Teixeira de Andrade (2015)
In this dissertation, the idea of the ludic in Friedrich Schiller, Johan Huizinga, Hans-Georg Gadamer and Roger Caillois will interact to each other and to Julio Cortázar's book Último Round playing a game of reflexes and reflections. By this game, we will raise a discussion about the importance of the ludic for culture, for arts and especially for literature.